Gambaran Kejadian Obesitas dan Faktor-Faktor yang Memengaruhi pada Usia di Atas 40 Tahun di Kelurahan Tanjung Duren Jakarta Tahun 2016 - Abdul Siddiq Bin Rahani; Ernawaty Tamba (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2018)
Obesity in adulthood is important to be considered due to its association with various diseases such as coronary heart disease. This study aimed to determine the incidence of obesity in adults and its affecting factors such as age, gender, education level, occupation, frequency of eating per day, total calories consumption per day, level of physical activity and parental obesity status. This was a cross sectional study with analytic observational approach. The study was carried out in 2016 among adults aged above 40 years old residing in Kelurahan Tanjung Duren, Jakarta. Primary data were obtained through interviews and questionnaires. Weight and height measurements were taken to assess the Body Mass Index (BMI) of the respondents. The study found that 44 (41,12%) of the respondents were obese (BMI ≥ 25 kg/m2). Chi-square analysis between obesity and independent variables showed that the incidence of obesity was negatively related to gender (p = 0.351), age (p = 0,520), education level (p = 0.352), occupation (p = 0.141), physical activity (p = 0,220), and parental obesity status (p = 0,109). Two variables were observed to have a positive relationship with the incidence of obesity, i.e. meal frequency per day (p = 0.029) and total calories consumption per day (p = 0,000). This study recommends obese adults to have healthy diet and run appropriate physical activities to reduce the incidence of obesity and avoid obese-related diseases.Keywords: Obesity, Body Mass Index (BMI), Adults